Bank Corporate Governance: Shield Against Fraud - Kulmie, Dayah Abdi; Ibrahim, Mohamed Salad (Journal of Ecohumanism, 2024)
An efficient corporate governance system in a bank is crucial for maintaining financial stability, boosting stakeholder confidence, promoting corporate accountability, and mitigating fraud risks. This paper investigates the role of bank corporate governance in safeguarding against fraud, reviwing 20 artciles published from 2017-2024. The study belives that fraud in banking institutions is a significant threat to the financial system, causing financial hardship and disrupting the banking system, indicating that opportunity such poor governance, weak control systems, poor organizational culture is the most contributing factor of these illegal and unethical behavior. The paper found that strong corporate governance significantly reduces the risk of fraud, with the board and audit committee playing a crucial role in ensuring accountability and boosting governance. To achieve bank corporate governance goals, it is necessary to utilize all available resources, including human and technological resources. The paper also found that corporate governance brings benefits such as increased transparency, accountability, reduced risk, enhanced decision-making, compliance, ethical conduct, and improved brand value, underlying that fraud risk incurs financial costs, reputational and regulatory risks, and decreased employee efficiency. The review concludes that bank corporate governance can act as shield against fraud, adding that ethical leadership, focusing on transparency and accountability, is essential for effective governance and deterring bank fraud. The study suggests investigating various types of fraud in the banking sector and their correlation with corporate governance, as well as conducting longitudinal studies to assess the long-term effects of robust corporate governance. Originality/contribution: The study asserts that effective governance is crucial for banks to become secure, stable, and robust. It emphasizes the importance of the board, audit committee, and moral leadership as crucial elements, and offers a how bank fraud is mitigated through good bank governance.